Metaphysics, sophistry, and illusion : toward a widespread non-factualism - Balaguer, Mark, 1964- (Oxford University Press, 2021)
Metaphysics, Sophistry, and Illusion introduces a novel kind of non-factualist view, and argues that we should endorse views of this kind in connection with a wide class of metaphysical questions. It also explains how these non-factualist views fit into a general anti-metaphysical view called neo-positivism.